Fundamental methods of mathematical economics - Chiang, Alpha C. (McGraw-Hill/Irwin, 2005)
It has been twenty years since the last edition of this classic book. Kevin Wainwright (British Columbia University and Simon Fraser University), a long time user of the text, has executed the perfect revision: he has updated examples, applications and theory without changing the elegant, precise presentation style of Alpha Chiang. Readers will find the wait was worthwhile.